Isolation and Characterization of a Bacteriophage That Hosts on Avian-pathogenic Escherichia coli (APEC) - Fakhouri, Haya; Juneidi, Orjowan; Al Mohtaseb, Hana; Ishnaiwer , Murad; Al-Razem, Fawzi (International Journal of Poultry Science, 2019)
Background and Objective: Infectious Colibacillosis disease caused by Avian-pathogenic Escherichia coli (APEC) commonly threatens poultry flocks worldwide. It limits productivity and causes severe economic losses to poultry sector. In addition, the emergence of multidrug resistance among APEC is an increasing concern since these resistant bacteria can infect humans and develop mechanisms that enable them to resist the commonly used antibiotics. The use of phages in treating pathogenic bacteria is considered a possible alternative to the conventional use of antibiotics. The aim of this study was to isolate and characterize APEC E. coli bacteriophage and to determine its cyclic replication through double layer test and one step growth curve. Materials and Methods: Bacteriophage was isolated from poultry feces samples using soft agar overlay method and was detected through the formation of clear zones on a lawn culture of APEC host bacterium on Luria Bertani (LB) agar plates. The phage total proteins analysis was carried out using SDS-PAGE through which samples were electrophoresed on a 10% polyacrylamide gel. The quantification of infectious viruses in bacterial suspension was determined through a one-step growth curve analysis using double layer test. The host range of the bacteriophage was further explored by performing spot tests with four APEC bacterial strains. Results: An APEC E. coli Bacteriophage was isolated. It was found to possess an apparently 17 kb genome size. The SDS-PAGE showed two major visible protein bands of 30 and 50 KDa. The phage was capable of lysing four tested APEC strains, an indicative of wide host range for the isolated bacteriophage. One step growth curve showed a phage latent period of about 24 h, burst period of 70 h and a burst size of about 2.4×104 plaque forming units (PFU) per plaque. Conclusion: A bacteriophage targeting four APEC strains has been isolated. It could be used to eliminate or reduce the scope of APEC infection in poultry and possibly used as an alternative to antibiotics.